2019
DOI: 10.3390/agronomy9100654
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Difference between the Day and Night Temperatures Can Enhance the Quality of Astragalus membranaceus and Codonopsis lanceolata Plug Seedlings

Abstract: Astragalus membranaceus Bunge and Codonopsis lanceolata Benth. et Hook. f. are two famous medical species in Korea, China, and Japan, mainly used for treating diseases including cancer, obesity, and inflammation. Manipulation of the difference between the day and night temperatures (DIF) is an efficient horticultural practice to regulate the growth and development of vegetables in a glasshouse. However, little research has focused on how the DIF influences the plug seedling quality of medicinal plants. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Chlorophyll, an essential component of the light-harvesting complex, plays a crucial role in capturing and transferring photons to the reaction center of the photosystem in the primary reaction [ 29 ]. The chlorophyll can be degraded by abiotic or biotic stresses such as heat, chilling, and drought [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll, an essential component of the light-harvesting complex, plays a crucial role in capturing and transferring photons to the reaction center of the photosystem in the primary reaction [ 29 ]. The chlorophyll can be degraded by abiotic or biotic stresses such as heat, chilling, and drought [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, the effects of DIF regulation on growth were predictable ( Figure 7 ). This prediction method in conjunction with specific growing conditions and/or crop species might be important for practical application in horticulture ( Kläring and Schmidt, 2017 ; Liu et al, 2019 ). However, as a limitation of this, other situations such as the 12/12 h temperature cycles were not addressed in this study, and further studies are required to determine the growth regulation of DIF.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Liu et al [61] have mentioned that enrichment with CO 2 (1050 µmol mol −1 CO 2 ) and supplementary lighting (100 µmol m −2 s −1 ) can improve the quality of plants, by promoting a higher photosynthetic activity and increasing their total carbohydrate content. Similarly, Liu et al [96] have reported that DIFs of 0 • C or >10 • C substantially increase the content of primary and secondary metabolites in A. membranaceus and C. lanceolata seedlings. In addition, Liu et al [97] found that the physiological quality of different medicinal species improves at a night temperature of 15 • C due to an increase in CO 2 assimilation and in the synthesis of carbohydrates, including soluble sugars, starch, total phenols, and flavonoids.…”
Section: Seedling Extraction Easementioning
confidence: 71%
“…The SDM/H ratio has been used to predict plant quality in different medicinal species [96,97] and in horticultural crops [6]. Recently, Bantis et al [5] evaluated different quantitative criteria for producing quality plants and found that the SDM/H ratio is one of the best indicators for predicting the physiological and commercial quality of watermelon and interspecific squash seedlings.…”
Section: Shoot Dry Matter/plant Height Ratiomentioning
confidence: 99%
See 1 more Smart Citation